Hepatic vascular malignancies in children are associated with increased rates of surgical resection and improved overall survival compared with adults. Issue 5 (4th March 2021) - Commander, Sarah Jane; Cerullo, Marcelo; Leraas, Harold J.; Reed, Christopher R.; Achey, Meredith A.; Wachsmuth, Lucas P.; Schooler, Gary R.; Tracy, Elisabeth T.
Abstract: Background: Hepatic vascular malignancies (HVMs) are rare malignancies, with no standardized treatment regimens. The most common HVMs, angiosarcoma and malignant epithelioid hemangioendothelioma (EHE), are often grouped together in the literature complicating our ability to achieve reliable survival data and treatment strategies. Objective: To compare the disease characteristics of HVMs, with a subanalysis on pediatric patients. Methods: The 2016 National Cancer Database was queried for patients with HVMs using international classification of diseases‐oncology‐3 (ICD‐O‐3) codes yielding 699 patients. Descriptive statistics, chi‐square, Kaplan‐Meier, and log‐rank analyses were performed. Results: We found 478 patients (68%) with angiosarcoma and 221 (32%) with EHE. The median (Q1, Q3) age for angiosarcoma patients was 65 years (56, 75) versus 54 years (37, 65) in EHE patients ( P < .001). The rate of resection was lower in patients with angiosarcoma than EHE (13% vs 32%, P < .001). The mean 1‐, 3‐, and 5‐year overall survival for angiosarcoma patients was 17%, 8%, and 6%, respectively, versus 80%, 65%, and 62% in EHE patients ( P < .0001). A subgroup analysis was performed on pediatric patients demonstrating six with angiosarcoma and 10 with EHE. The mean 1‐, 3‐, and 5‐year overall survival for pediatric angiosarcoma patients was 67%, 50%, and 50%, respectively, and 90%, 90%, and 90% for pediatric EHE patients. Conclusion: In the largest study of HVMs to date, we found angiosarcoma has significantly worse overall survival than EHE. Pediatric patients appear to have improved survival and higher rates of resection. Larger studies of HVMs are needed to clearly differentiate tumor types, standardize care, and improve survivorship.